Designing the Decision Support System to Determine the Major and Higher Education Institution based on Preferences of Prospective Students - Astutik, Siti Supri; Jatiningrum, Wandhansari Sekar (Spektrum Industri, 2023)
There are several factors considered by students toward determining the major and higher education institution. As a result, determining the best choices for further studies becomes difficult. Moreover, there are many choices of higher education. This study contributes to developing a decision support system (DSS) to help students determine the major and higher education institution considered several criteria based on Analytical Hierarchy Process (AHP). Several criteria and subcriteria were chosen by distributing 186 questionnaires to final grade students. Based on the result, criteria and subcriteria used were tuition fee, scholarship, infrastructure (library, classroom, laboratory, transportation, teaching staff), curriculum, quality (accreditation, study period, achievement), reputation, and international collaboration. According to these criteria and sub-criteria, a DSS was built to help students determine their major and higher education institution according to their preferences. The algorithm used was AHP, which was then built with Borland Delphi. Context Diagram, Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD) were made as a guide to design the DSS. This DSS was tested using black box test, beta test and compatibility test with manual calculations. The black box test showed that the DSS has performed the functions according to the design. Later, the beta test resulted in a correctness score of 20.4, reliability of 16.8, usability of 25.5, which means they were in the very good category and integrity of 3.4, which means good. Meanwhile, based on manual calculations, the DSS provides output in accordance with the results of manual calculations. Finaly, he DSS was proven to be used as a decision-making tool in determining the major and higher education institution for students